Application of Stool-PCR test for diagnosis of Helicobacter pylori infection in children - Falsafi, Tahereh (The WJG Press and Baishideng, 2009)
AIM: To evaluate the usefulness of stool-PCR test for diagnosis of Helicobacter pylori (H pylori) infection in pediatric populations. METHODS: Based on endoscopic features (including nodular gastritis, erosive duodenitis and ulcer) and/or a positive rapid urease test (RUT) obtained during endoscopy, 28 children from a group of children admitted to the Children's Medical Center of Tehran for persistent upper gastrointestinal problems were selected to compare biopsy-based tests with stool-PCR. Their gastric activity and bacterial density were graded by the updated Sydney system, and their first stool after endoscopy was stored at -70°C. Biopsies were cultured on modified campy-blood agar plates and identified by gram-staining, biochemical tests, and PCR. Two methods of phenol-chloroform and boiling were used for DNA extraction from H pylori isolates. Isolation of DNA from stool was performed using a stool DNA extraction kit (Bioneer Inc, Korea). PCR was performed using primers for detection of vacA, cagA, and 16srRNA genes in both isolates and stool. RESULTS: Sixteen out of 28 child patients (57%) were classified as H pylori positive by biopsy-based tests, of which 11 (39%) were also positive by stool-PCR. Sensitivity and specificity of stool-PCR was 62.5% and 92.3% respectively. H pylori was observed in histological sections for 10 out of 11 stool-positive patients. Association was observed between higher score of H pylori in histology and positivity of stool-PCR. Also association was observed between the more severe form of gastritis and a positive stool-PCR. CONCLUSION: Association between higher score of H pylori in histology and a positive stool-PCR make it a very useful test for detection of H pylori active infection in children. We also suggest that a simple stool-PCR method can be a useful test for detection of H pylori virulence genes in stool.